2022
DOI: 10.3390/cells11132064
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Antioxidant and Lipid Handling Protein Expression Influence How Cells Expressing Distinct Mutant TP53 Subtypes Maintain Iron Homeostasis

Abstract: The tumor suppressor TP53 is the most commonly mutated gene in human cancers, and iron is necessary for cancer cell growth and proliferation, but there is a significant gap in knowledge for how the two cooperate to affect cellular physiology. Elucidating this role is complicated, however, because each TP53 mutation subtype exhibits unique phenotypic responses to changes in iron availability. The goal of this work was to determine how cells expressing distinct TP53 mutation subtypes respond to iron restriction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The context-dependent differences in IRP involvement are likely multifaceted. Factors such as mode of ferroptosis induction ( Gryzik et al, 2021 ), metabolic state of the cell ( Novera et al, 2020 ), and differences in endogenous antioxidant capacities ( Cardona et al, 2022 ) that influence the ability to handle a given amount of labile iron could all contribute to IRP responsiveness. Regardless, increased IRP-IRE binding activity ( Chen et al, 2020 ), and even the increased expression of either IRP1 ( Yao et al, 2021 ; Zhang et al, 2022 ) or IRP2 ( Li et al, 2020 ) alone have been shown to augment ferroptosis sensitivity ( Figure 2 ).…”
Section: Iron and Irps In Ferroptosismentioning
confidence: 99%
“…The context-dependent differences in IRP involvement are likely multifaceted. Factors such as mode of ferroptosis induction ( Gryzik et al, 2021 ), metabolic state of the cell ( Novera et al, 2020 ), and differences in endogenous antioxidant capacities ( Cardona et al, 2022 ) that influence the ability to handle a given amount of labile iron could all contribute to IRP responsiveness. Regardless, increased IRP-IRE binding activity ( Chen et al, 2020 ), and even the increased expression of either IRP1 ( Yao et al, 2021 ; Zhang et al, 2022 ) or IRP2 ( Li et al, 2020 ) alone have been shown to augment ferroptosis sensitivity ( Figure 2 ).…”
Section: Iron and Irps In Ferroptosismentioning
confidence: 99%